A harmonised European training syllabus for thoracic surgery: report from the ESTS/ERS task force group. Issue 6 (14th June 2018) - Massard, Gilbert; Tabin, Nathalie; Mitchell, Sharon; Batirel, Hasan; Brunelli, Alessandro; Elia, Stefano; Frick, Anna; Huertgen, Martin; Lerut, Antoon; Molins, Laureano; Papagiannopoulos, Kostas; Subotic, Dragan; et al.
As has been reported for respiratory medicine, a high variance exists among European countries in the content and modes of delivery for specialty training in thoracic surgery. According to a survey by the Union Européenne des Médecins Spécialistes (UEMS; European Union of Medical Specialists) section of thoracic surgery conducted in 2013, disparities begin at the certifying body level: the specialist diploma is delivered by the ministry of health in half of the countries, and by various other authorities in the remaining countries [1]. Additionally, the designation of the specialty differs considerably: in 13 countries, thoracic surgery is practised as a monospecialty; in eight countries, it is combined with cardiac surgery; and in two countries (Belgium and Luxembourg), the designation does not exist. A harmonised European training syllabus for thoracic surgery is now available http://ow.ly/xQMP30iZ50E